Fast-Track Legislation Mechanism as an Alternative to the Formation of Legislation in Indonesia - Agnes Fitryantica; Regy Hermawan (Jurnal Ilmiah Kebijakan Hukum, 2022)
The formation of laws and regulations that take a short time to be formulated may have procedural defects in the process of their formation, such as procedural violations, non-implementation of one or several procedures for their formation and insufficient quality of implementation of the procedures for their formation. Consequently, the legislative process in Indonesia leads to poor conditions, causing problems in the formation of laws and regulations. The practice of making laws and regulations in a short period carried out by the legislature seems to apply the mechanism of fast-track legislation. However, this fast process is not in accordance with the positive law that regulates it. Therefore, the mechanism of fast-track legislation is seen as an alternative to the formation of laws and regulations to prevent the practice of forming bad laws and regulations from being repeated continuously. This research is normative juridical research, with a statutory approach and a comparative law approach. This research journal aims to examine the effectiveness of the fast-track legislation mechanism when used as an alternative to the formation of legislation in Indonesia.